Borges and his approach to East Asia: A barbarian in Asia - Zhang, Lan (Estudios Complutenses de Asia Oriental, 2025)
In this article, we try to discover how Borges approaches the literature and metaphysics of East Asia, in particular, those of China and Japan, through the reading, as well as his peculiar facet as a twentieth-century Latin American Orientalist. We will analyze his contact with Oriental world from his childhood education in his father's English library, through his youth in Geneva, where he became interested in Buddhism and Taoism. On the other hand, through his publications in the 1930s and 1940s in Argentinean magazines, we will observe his literary taste for canonical Chinese and Japanese works, which were marginal in Argentina at THAT period. Finally, we will discuss Borges' interesting view on the theory of civilization and barbarism and his claim to be a "barbarian in Asia".
Keywords: Jorge Luis Borges; China; Japan; civilization and barbarism; Orientalism